TWO NEW RECORDS OF ANTHIINE FISHES GENUS PLECTRANTHIAS (PERCIFORMES: SERRANIDAE) FROM INDONESIA - Peristiwady, Teguh; Makatipu, Petrus Ch.; Satrioajie, Widhya Nugroho; Wibowo, Kunto (Marine Research in Indonesia, 2014)
Three specimens of Plectranthias retrofasciatus Fourmanoir and Randall, 1979 and one specimen of P. randalliÃÂ Fourmanoir and Rivaton, 1980 were collected by first author from fish market, Bitung, North Sulawesi on JuneÃÂ and September 2010. The specimens were deposited at LBRC-F, the reference collection of LIPI Bitung, TechnicalÃÂ Implementation Unit for Marine Biota Conservation, Research Centre for Oceanography, Indonesian Institute ofÃÂ Sciences, Bitung, Indonesia. Plectranthias retrofasciatus is closely related to P. megalophthalmus and P. knappi,ÃÂ in sharing some morphological characters as snout length and interorbital width, while P. randalli differs to otherÃÂ species by having a moderate deep body proportion. Initially these species known only from New Caledonia for P.ÃÂ retrofasciatus and Chesterfield Islands and southern Taiwan for P. randalli respectively. The two species of anthiineÃÂ fishes collected from Bitung, Indonesia bringing the total number of species of this genus known in Indonesia to six.